2022
DOI: 10.3390/ijms23137352
|View full text |Cite
|
Sign up to set email alerts
|

Macro- and Nanoscale Effect of Ethanol on Bovine Serum Albumin Gelation and Naproxen Release

Abstract: We report extended ethanol-induced gelation procedures of bovine serum albumin (BSA) at 37 °C and investigate the release behavior of a spin-labeled naproxen derivative (SL-NPX) from these hydrogels. The macroscopic mechanical properties of these gels during formation were studied using rheology, while a nanoscopic, more molecular view was obtained by analyzing the secondary structure of the protein during gelation via infrared (ATR-IR) spectroscopy. To evaluate the potential use of BSA hydrogels in controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Gel structures which yield percolating pore networks (e.g. low monomer volume fractions) 90 are important for applications where diffusion through the gel is important, such as in drug delivery and nutrient accessibility for in cell-seeded gels 40,[92][93][94][95][96][97][98] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gel structures which yield percolating pore networks (e.g. low monomer volume fractions) 90 are important for applications where diffusion through the gel is important, such as in drug delivery and nutrient accessibility for in cell-seeded gels 40,[92][93][94][95][96][97][98] .…”
Section: Discussionmentioning
confidence: 99%
“…low monomer volume fractions) 90 are important for applications where diffusion through the gel is important, such as in drug delivery and nutrient accessibility for in cellseeded gels. 40,[92][93][94][95][96][97][98] Pore size and distribution are important considerations in tissue engineering, for example where certain cell types need pores of particular sizes for effective growth and tissue regeneration. 99,100 Being able to control and reproduce the properties of porous gel structure is important for regulating seeded cell properties and behaviour, including proliferation, migration, differentiation and phenotypic variation.…”
Section: Discussionmentioning
confidence: 99%
“…However, its use is limited by the fact that it requires the covalent modification of the molecule with a stable radical (EPR-active group). Regarding the investigation of hydrogels, EPR spin labeling has been previously shown to be useful for controlled release studies of TEMPO-labeled coumarin-3-carboxylic acid and warfarin [36], and a spin-labeled naproxen derivative [37] from bovine serum albumin (BSA)-based hydrogels, as well as the cytotoxic ligand HL used as the model molecule for the release behavior of hydrophobic drugs from the human serum albumin (HSA) hydrogels [38]. Spin-labeled stearic acid (16-DS) has been utilized as a model molecule for the release behavior of amphiphilic drugs from BSA hydrogels [39], as well as for the confirmation of the existence of basic molten globule states of BSA hydrogels [40].…”
Section: Introductionmentioning
confidence: 99%
“…Sanaeifar et al studied the interaction of spin-labeled naproxen derivative (SL-NPX) with bovine serum albumin (BSA) hydrogels [ 8 ]. It has been found that the rate of SL-NPX release from BSA hydrogels can be controlled by ethanol concentration, BSA concentration, incubation time, and initial drug loading percentage.…”
mentioning
confidence: 99%